Haploidentical stem cell donor choice for patients with acute myeloid leukemia: a study from the ALWP of the EBMT - Sanz, Jaime; Labopin, Myriam; Blaise, Didier; Raiola, Anna Maria; Busca, Alessandro; Vydra, Jan; Tischer, Johanna; Chevallier, Patrice; Bramanti, Stefania; Fanin, Renato; Socié, Gérard; Forcade, Edouard; et al. (Blood advances, 2024)
There is a paucity of information to guide the selection of the most suitable donor in haploidentical (Haplo) hematopoietic stem cell transplantation (HSCT). For this reason, from the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation, we conducted a retrospective analysis to evaluate the impact of Haplo donor characteristics on outcomes in patients with acute myeloid leukemia (AML) who received graft-versus-host disease prophylaxis with posttransplant cyclophosphamide (PTCy). The primary end point was graft-versus-host disease (GVHD)-free and relapse-free survival (GRFS). Overall, 2200 patients were included. The median age of donors was 37 years (range, 8-71); 820 (37%) were females, including 458 (21%) who were used for male recipients. In addition, 1631 donors (74%) donated peripheral blood (PB). Multivariable analysis identified certain donor-related risk factors with a detrimental impact on transplant outcomes. The use of PB, older donors' ages (>37 years), and female donors to male recipients negatively affected GRFS. Donor's age and female donor-to-male recipient combination also affected nonrelapse mortality, leukemia-free survival, and overall survival. In conclusion, donor-related variables significantly influence outcomes in patients with AML after Haplo-HSCT with PTCy. When possible, younger donors and male donors for male recipients should be prioritized. The use of bone marrow can additionally prevent GVHD.
Keywords: senioři; Tissue Donors; dárci tkání; Retrospective Studies; mladiství; Transplantation, Haploidentical; Middle Aged; mužské pohlaví; nemoc štěpu proti hostiteli; Leukemia, Myeloid, Acute; Adult; mladý dospělý; Donor Selection; dítě; Child; Hematopoietic Stem Cell Transplantation; Young Adult; ženské pohlaví; transplantace hematopoetických kmenových buněk; retrospektivní studie; haploidentická transplantace; Humans; Graft vs Host Disease; výběr dárců; lidé středního věku; akutní myeloidní leukemie; dospělí; Female; Aged; Adolescent; lidé; Male